Legal Pregnancy Interruption due to Sexual Violence in a Public Hospital in the South of Brazil - Vitoria Finger Trapani; Otto Henrique May Feuerschuette; Alberto Trapani Júnior (Revista Brasileira de Ginecologia e Obstetrícia, 2023)
Abstract Objective To analyze the cases of all women who attend to a service of legal termination of pregnancy in cases of sexual violence in a public reference hospital and to identify the factors related to its execution. Methods Cross-sectional observational study with information from medical records from January 2014 to December 2020. A total of 178 cases were included, with an evaluation of the data referring to the women who attended due to sexual violence, characteristics of sexual violence, hospital care, techniques used, and complications. The analysis was presented in relative and absolute frequencies, medians, means, and standard deviation. Factors related to the completion of the procedure were assessed using binary logistic regression. Results Termination of pregnancy was performed in 83.2% of the cases; in 75.7% of the cases, the technique used was the association of transvaginal misoprostol and intrauterine manual aspiration. There were no deaths, and the rate of complications was 1.4%. Gestational age at the time the patient's sought assistance was the determining factor for the protocol not being completed. Pregnancies up to 12 weeks were associated with a lower chance of the interruption not occurring (odds ratio [OR]: 0.41; 95% confidence interval [CI]: 0.12–0.88), while cases with gestational age > 20 weeks were associated with a greater chance of the interruption not happening (OR: 29.93; 95%CI: 3.91–271.50). Conclusion The service studied was effective, with gestational age being the significant factor for resolution.